RETRACTED: NEAT1 Overexpression Indicates a Poor Prognosis and Induces Chemotherapy Resistance via the miR-491-5p/SOX3 Signaling Pathway in Ovarian Cancer - Jia, Xinzhuan; Wei, Lan; Zhang, Zhengmao (Frontiers in Genetics, 2021)
Background: Accumulated studies have reported that dysregulated long noncoding RNAs (lncRNAs) are crucial in ovarian cancer (OC) initiation and development. However, detailed biological functions of lncRNA NEAT1 during the progression of OC remains to be uncovered. Purpose: Our aim was to identify the role of NEAT1 in cisplatin resistance of ovarian cancer and the underlying mechanisms. Methods: The expression patterns of NEAT1 in OC cell lines and tissue samples were identified by qRT-PCR. The cisplatin (DDP) sensitivity of OC cells was detected by MTT and CCK8 assay, while OC cell apoptosis and cell cycle were detected using flow cytometer assays. In addition, effects of NEAT1 on tumor growth were determined by xenograft tumor model. Luciferase reporter assay was conducted to prove the regulatory relation of miR-491-5p, NEAT1, and SOX3. Importantly, the expression of NEAT1 in exosomes from cisplatin-resistant patients was also determined by using qRT-PCR. Results: In this study, upregulated NEAT1 was detected in OC cell lines and tissues. Meanwhile, NEAT1 was also increased in cisplatin-resistant OC cell lines and tissues. Upregulation of NEAT1 inhibited cisplatin-induced OC cell apoptosis and promoted cell proliferation, while knockdown of NEAT1 played the opposite role. These effects were also observed in vivo. Furthermore, direct interaction was observed between NEAT1 and miR-491-5p. NEAT1 led to the upregulation of miR-491-5p-targeted SOX3 mRNA. Importantly, this study also showed upregulated NEAT1 expression in serum exosomes derived from cisplatin-resistant patients. Conclusion: NEAT1 is vital in the chemoresistance of ovarian cancer through regulating miR-491-5p/SOX3 pathway, showing that NEAT1 might be a potential target for OC resistance treatment.